UMP and DRB-HICOM: A Mismatch of Expectations - Nabila , Abdul Malek; Normah, Othman (2012)
A survey in the form of a questionnaire was conducted on 40 academicians teaching at the Mechanical Engineering Faculty, Universiti Malaysia Pahang. The survey was to find out the academicians’ opinions about their faculty’s relationship with the DRB-HICOM industry. The survey was also to find out whether their job has any significant effect on the students’ performance at the automotive industry. The results show that there is mismatch between the DRB-HICOM’s and UMP’s expectations on the students’ overall performance in the industry. This paper discusses the mismatch.